Examining The Impact of the Youth Employment Agency (Yea) in the Fourth Republic: A Case Study of the Role of the Ghanaian Youth Towards Community Policing Under the Sixth Module - Ibrahim, B. (University of Ghana, 2020)
Youth unemployment, including its related challenges (e.g., crime), is one of the major challenges facing many countries in the world. Youth unemployment, for example, remains a major challenge in Europe, Asia, Australia, Latin America, North America and, of course, Africa. In response, the government of Ghana established the Youth Employment Agency (YEA) to deal with youth unemployment and its related challenges in 2015. One of the modules which was designed to directly deal with youth unemployment and its related challenges is the 6th module which concerns itself with the “Youth in Community Service and Security Module” [otherwise known as “Community Protection Assistants—CPAs”]. The study was designed to appraise and measure the 6th module—the “Youth in Community Service and Security Module” (otherwise known as “Community Protection Personnel”)—against YEA’s objectives using the mixed method. The results showed that YEA works to offer the youth with temporary employment and connects them to lifelong employments through its Job Portals and Job Centre. Moreover, interactions with YEA top officials and CPAs showed that YEA provides the CPAs with ‘Exit-Fund’ at the end of the two-years-stay on the program. Still, a larger proportion (80.6%) of the CPAs believed that they have been able to reduce crime in the communities under study. Equally, a greater proportion of the community-residents who know about the work of the CPAs (i.e., 56% of them) confirmed that there was a reduction of crime in the communities due to the activities of the CPAs. However, low salary and lack of funding have generally destabilized operation as most of them are unable to feed themselves and families well, rent and renew rents and transport themselves to and fro.
MA. Political Science
Keywords: Youth Employment Agency (YEA); Ghana; Community Protection Assistants (CPA)